The Role of Technology Innovation and Movements of Additional Plants in Rice Production Improvement - Dedi Sugandi; Wahyu Wibawa (Fakultas Pertanian, Universitas Janabadra, 2017)
Studies done to investigate role and implementation level of technological innovation and LTT movement in increasing rice production in Bengkulu Province, and to propose suggestions and alternative policies related to application of technological innovation and LTT. Study carried out from September 2015 to June 2016. Primary data obtained by collecting data of LTT and application of technological innovation periodically per quarter (April up to September, October up to March). Particularly for LTT data, it was collected on a day basis. Secondary data collected by both communication and reference from stakeholders. Results: implementation of UPSUS has been capable of increasing productivity by 0.29 ton per ha, obtained from increasing application of technological innovation in forms of VUB, recommended fertilizer dosage, fertilization frequency, and jajar legowo by 12.17 up to 18.47 percent, 8.99 up to 12.77 percent, 4.51 up to 8.04 percent, and 18.64 up to 22.48 percent, respectively. Implementation of UPSUS also increased LTT by 43,145 ha or equivalent to 34.53 percent and increased IP from 129.82 to 174.65, so that production also increased by 212,277 ton. Key-words: innovation, LTT, Production